Fatigue and the Female Nurse: A Narrative Review of the Current State of Research and Future Directions - Brennan J. Thompson (Mary Ann Liebert, 2021)
Background: The female nurse exhibits a multitude of personal and environmental characteristics that renders this population especially prone to fatigue. The consequences of fatigue in nurses are widespread and impactful at the personal, organizational, and societal levels. These include high injury rates and burnout in the nurse and poor patient and organizational outcomes. Objective: This article discusses the implications of fatigue in female nurses, including the impacts of fatigue across multiple entities (e.g., worker, patient, organization). It also reviews the current state of the research, including recent work on nurse fatigue and work schedule characteristics, and key areas for future work that would help empirically establish approaches to counter the detrimental and widespread effects of fatigue. Method: A narrative literature review was conducted resulting from an analysis of the literature limited to peer-reviewed studies. Results: A confluence of factors combines to elevate the prevalence and risk of fatigue in the female nurse. Numerous measures have established that performance-based fatigue results from nursing work schedules in nurses. Data also demonstrate that fatigue accumulates across successive shifts. Recent evidence supports the use of objective fatigue measures, including psychomotor reaction time and muscle function-related variables. Current gaps in the literature are delineated in the text. Conclusions: Strategic and well-designed research studies, as well as recent technological advances in fatigue tracking tools have the potential to help workers, administrators, and organizations develop fatigue management programs that could reduce the heavy burdens of fatigue on a multitude of health, safety, and economical outcomes.